Implementation Of E-Payment And The Influence On Service Levels And Internal Business Processes Of MSMEs In Bandar Lampung - D Pentiana; Nurmala, Nurmala; Anggraini, Depita; Mareta , Fitri; Ridwansyah, Eksa (Politeknik Negeri Bengkalis, 2024)
The objective of this research is to find out how e-payment is implemented in MSMEs in Bandar LampungCity, and how the application of e-payment affects MSME services in Bandar Lampung City, as well as how the effect ofimplementing e-payment on the internal business processes of MSMEs in Bandar City Lampung. The type of data usedin this research is primary data, namely interviews with MSME owners in Bandar Lampung City, Lampung, which is thepopulation in this research. The focus of this research is to find out how e-payment is implemented and its impact on thelevel of service and internal business processes of MSMEs. The analytical method used is simple regresion. The resultsof the study indicate that the application of e-payment has a positive effect on the level of service, but it does not affectthe internal business processes of SMEs in Bandar Lampung City.